2020
DOI: 10.1177/1535370220909332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peritoneal dialysis solution with different pyruvate concentrations on intestinal injury

Abstract: To investigate the effects of direct peritoneal resuscitation with pyruvate-peritoneal dialysis solution (Pyr-PDS) of different concentrations combined with intravenous resuscitation on acid–base imbalance and intestinal ischemia reperfusion injury in rats with hemorrhagic shock. Sixty rats were randomly assigned to group SHAM, group intravenous resuscitation, and four direct peritoneal resuscitation groups combined with intravenous resuscitation: group NS, LA, PY1, and PY2, that is, normal saline, lactate-PDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Shostak et al reported that pyruvate could improve the peritoneal dialysate-induced inhibition of proliferation in HPMCs ( 17 ). These results were supported by other similar study ( 18 ). We also found a specific scavenger for H 2 O 2 , namely catalase, which can improve the inhibition of cell growth.…”
Section: Discussionsupporting
confidence: 92%
“…Shostak et al reported that pyruvate could improve the peritoneal dialysate-induced inhibition of proliferation in HPMCs ( 17 ). These results were supported by other similar study ( 18 ). We also found a specific scavenger for H 2 O 2 , namely catalase, which can improve the inhibition of cell growth.…”
Section: Discussionsupporting
confidence: 92%
“…According to previous works, pyruvate was substantiated to improve the glycolytic energy generation and oxygen-carrying capacity of red blood cells during bypass surgery and storage, in vitro 39,40 . Pyruvate improved the blood pO 2 during intestinal ischemia reperfusion, reducing ischemia reperfusion injury in rats 41 . A small dose of pyruvate in cardioplegia for cardiac bypass surgery showed robust cardioprotection although there is no data that pyruvate effects on the normal human heart during exercise 42 .…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, early studies documented that pyruvatebased PDS (P-PDS) was much more effective than regular commercial lactate-based PDS (L-PDS) in improving human blood neutrophils' intracellular pH and superoxide generation (79,80). Regarding direct peritoneal resuscitation, recent animal studies also found that P-PDS was significantly advantageous over L-PDS in reversing visceral hypoperfusion, correcting metabolic acidosis, and protecting the intestinal barrier (81)(82)(83). Furthermore, as an example of colloids, pyruvate as a novel carrier in HES 130/0.4 significantly demonstrated kidney protection (as well as the intestinal barrier preservation: unpublished data) in the fluid resuscitation of rats subjected to lethal burn shock, compared to regular carriers in commercial HES 130/0.4 products (21).…”
Section: Pyruvate Saline Superior To Normal Salinementioning
confidence: 99%